Current Research Status of Traditional Chinese Medicine in Functional Constipation - Zhang, Pengnian; Zhang, Wei; Yu, Tao (Journal of Contemporary Medical Practice, 2025)
Functional constipation is a clinical syndrome characterized primarily by prolonged defecation time, reduced frequency of bowel movements, or dry and hard stools that are difficult to pass. It is a type of functional bowel disorder. Due to its lingering course, complex symptoms and signs, involvement of multiple Zang-fu organs, and lack of a unified treatment standard, it is considered a refractory disease. Traditional Chinese Medicine has documented constipation since ancient times. Modern TCM practitioners have innovated and developed treatment methods based on classical theories. This article aims to summarize the clinical treatment methods of TCM for functional constipation, providing new ideas for modern medicine in treating this condition.